Implementation of Integrating Information and Communication Technology (ICT) in the Classroom in Secondary Schools in Sri Lanka - Lindakumbura, V.; Embekke, E.K.S.K. (University of Jaffna, 2012)
Implementation of integrating information and communication technology (ict) in the classroom in secondary schools in sri lanka
Keywords: Information and Communication technology; Monitoring System